Nanoscale evolution of stress concentrations and crack morphology in multilayered CrN coating during indentation: Experiment and simulation - Werner Ecker; Jozef Keckes; Martin Krobath; Jakub Zalesak; Rostislav Daniel; Martin Rosenthal; Juraj Todt (Materials & Design, 2020)
The layered architecture approach allows designing mechanical and fracture properties of hard coatings. The current study investigates the performance of a multilayered CrN coating, consisted of 5 μm CrN sublayers of very similar mechanical properties and microstructure but different residual stress states, during in-situ wedge indentation. A finite element model of the indentation was developed and validated against measurements of the local multiaxial stress fields during indentation, characterized by means of X-ray nanodiffraction analysis with a spatial resolution of 500 nm. By means of numerical fracture mechanics the effect of the multilayered structure on the formation and morphology of mode II cracks is analyzed. The configurational force concept was applied to investigate the crack driving forces and crack extension angles of static cracks in different geometrical arrangements. The simulation results agree well with the experimental findings and reveal a shielding effect preventing an interface-near crack from entering the CrN layer with the higher compressive residual stresses. Furthermore, the possibility to match the numerical results with the locally resolved experiments allowed determining validated material parameters for the deformation and fracture behavior. The work revealed e.g. that a KIIC of around 1 MPa∙m1/2 is an appropriate choice for the investigated CrN coating. Keywords: X-ray nanodiffraction, CrN multilayered coatings, Residual stress, In-situ indentation, Configurational forces, Finite element modeling